Biobanking for cancer research: Preservation of tissue integrity – Some technical considerations - Shankar, S.K.; Mahadevan, Anita (Indian Journal of Neurosurgery, 2012)
Biobanking and biomarker discovery have become an integral part of neuro-oncology research. Towards achieving this end, the essential requirement is optimizing methods of tissue preservation of human tissues removed at surgery for diagnostic purposes and banking them for subserving future research. Owing to recent advances in molecular diagnostic tools, this clinical material has become a precious source for proteomic and genomic studies. The advent of biotechnological tools such as microarray, proteomics, and genomics has made it essential to preserve not just morphology but also the quality of nucleic acids and proteins, changing the traditional workflow of a pathology laboratory. It is therefore essential to develop simple technologies for tissue fixation and storage ensure that receptor and molecular integrity is reasonably maintained. Knowledge of the basic chemistry of tissue fixatives, the biochemical changes that take place in biological material by utilizing different techniques of fixation is essential while undertaking molecular, genomic, and proteomic studies on fresh and archival tissues.
Keywords: Formalin; formalin-free fixatives; molecular integrity of tissue; biobanking; neuro-oncology